Customer Acquisition, Business Dynamism, and Aggregate Growth - Ignaszak, Marek; Sedláček, Petr (Review of Economic Studies, 2026)
Abstract Business dynamism—the process of firm entry, growth and exit—lies at the heart of modern endogenous growth models. While productivity differences have traditionally been seen as the main driving forces of business dynamism, a growing body of evidence suggests that customer acquisition is at least as important. In light of this evidence, we propose a novel endogenous growth model in which innovating firms must first acquire customers to sell their products. Estimating our model with aggregate and firm-level data, we find that expansions of firms’ customer bases (market sizes) boost their incentives to innovate and shift resources towards high-growth businesses (“gazelles”). Combined, these effects explain over 40% of aggregate growth and substantially change predictions about the efficacy of growth policies. Finally, we document support for key model predictions using firm-level micro-data.